NOS4A2. Season 2 [videorecording (DVD)] - O'Brien, Jami (AMC Studios, RLJ Entertainment, 2020)
After eight years on life-support, Charlie Manx finally dies and the news hits Vic hard; she can't believe it's over ... and with good reason. Soon Manx is back and desperate for revenge against the woman who put him in critical condition, and her whole family -- but especially her son -- is under threat. Allies new and old on both sides are ready to battle for the future.